ELECTRONIC ROAD PRICING (ERP): A SYSTEMATIC MAPPING STUDY - Rizal, Muhamad; Purnomo, Margo; Maulina, Erna; Febrian, Achmad Fajri (JBFEM, 2018)
Electronic Road Pricing (ERP) has been used to reduce traffic in metropolitan cities. This system has proven to reduce the rate of vehicles entering the limited area effectively as well as increasing the rate of vehicles that use the highway around the limited area thus increasing the usefulness of the road. This article aims to classify, identify scientific publications, and conduct a thematic analysis of the current literature to create an extensive and detailed understanding. The results of this mapping are expected to contribute to both researchers and practitioners in determining the research focus gap and the next type of ERP research. Based on the results of the SMS on research in the field of ERP, it is found out that there are fifty empirical studies that meet the inclusion criteria. We classify fifty articles on the research focus areas underneath the categories: ERP, traffic congestion, road pricing, traffic management technology, transportation demand management. Then the studies are grouped into six categories: validation research, evaluation research, solution proposal, philosophical papers and experience papers. Afterall, this article also produces the categorization and quantification of current ERP studies in various dimensions as well as an overview of current research topics and trends.